PEMBELAJARANSNOWBALL THROWING DITINJAU DARIGAYA BELAJAR EKSTROVERT-INTROVERT - Sulaiman Sulaiman (Universitas Muhammadiyah Pringsewu, 2018)
ABSTRACT: The purpose of this study was to determine the results of students 'mathematics learning through cooperative learning model Snowball Throwingin terms of students' learning styles. The population of this research is all class VIII SMP Negeri 1 Adiluwih totaling 285 students. The sample was 70 students consisting of 35 students to a class of 35 students for the experimental and control classes were obtained by technique. cluster random sampling. The instrument used was a questionnaire and student mathematics achievement test. Data analysis techniques used a party t-test and t-test two parties. Based on t-test calculation of the two parties to the student's learning style extrovert, shows thitung = 3.07 and ttable = 2.021 at significance level of 5% that thitung > ttabel (3.07> 2,021), then H0 is rejected and  H1 received. For the t-test of the parties to the student's learning style extrovert show thitung = 3.07and ttabel = 1.684 at significance level of 5% that thitung > ttabel (3.07> 1.684), then H0  is rejected and  H1 accepted. T-test calculation of the two parties to the student's learning style introvert show thitung = -0.87 and ttabel = -2.069 at a significance level of 5% that thitung > ttabel (-0.87> -2.069), then H0 is  rejected and  H1  accepted. For the t-test for students' learning styles  introvertshow thitung = -0.87 and ttable = 1.714 at significance level of 5% that  thitung < ttabel   (-0.87 <1.714), then H0 is   rejected and H1 accepted. Key words: Snowball Throwing,learning style,ekstrovert, extrovert